HUBUNGAN KONSUMSI KOPI DAN KEBIASAAN MEROKOK TERHADAP PENINGKATAN TEKANAN DARAH PADA NELAYAN DI DESA WARULOR PACIRAN LAMONGAN - Fithri Fifianah; Detti Nur Irawati; Nenny Triastuti; M. Perdana Airlangga (Universitas Muhammadiyah Surabaya, 2023)
Abnormalities of blood pressure are divided into two kinds, namely as increased blood pressure or high blood pressure (hypertension) and low blood pressure (hypotension). Hypertension or commonly known as high blood pressure is a chronic medical condition in which the blood pressure in the arteries increases, requiring the heart to work harder to circulate blood through the blood vessels throughout the body. Hypertension is also called the